Strategies to enhance greenhouse strawberry yield through honeybee pollination behavior: a simulation study - Cao, Zhihao; Jiang, Shuo; Qu, Hongchun (Frontiers in Plant Science, 2024)
Strawberries are a widely cultivated greenhouse crop in China, primarily pollinated by honeybees, in accordance with traditional planting practices and local conditions. Extensive research has demonstrated that cross-pollination benefits numerous strawberry cultivars, leading to enhanced yield through the interplanting of different cultivars. However, the high costs associated with cultivation have hindered systematic research on the design of interplanting strategies. In this study, we utilized a simulation model to investigate how to leverage honeybee natural foraging behavior to improve pollination efficiency and explore fruit weight under various interplanting strategies within a greenhouse. Our findings indicate that adopting an alternating planting approach for different cultivars within the same bed effectively facilitates cross-pollination, leading to increased strawberry fruit yield. Additionally, dividing the strawberry plants into two batches and staggering their planting time helps mitigating the pressure of competition for bee pollination during peak blooming period, consequently contributing to enhanced yield. These proposed planting strategies offer valuable cultivation suggestions for farmers in some remote areas in China who still rely on honeybees as primary pollinators.